DETERMINATION OF GROWTH RATES AS AN INPUT OF THE STOCK DISCOUNT VALUATION MODELS - Momčilović, Mirela; Vlaović Begović, Sanja; Ercegovac, Dajana (International Journal of Economic Practice and Policy, 2014)
When determining the value of the stocks with different stock discount valuation models, one of the important inputs is expected growth rate of dividends, earnings, cash flows and other relevant parameters of the company. Growth rate can be determined by three basic ways, and those are: on the basis of extrapolation of historical data, on the basis of professional assessment of the analytics who follow business of the company and on the basis of fundamental indicators of the company. Aim of this paper is to depict theoretical basis and practical application of stated methods for growth rate determination, and to indicate their advantages, or deficiencies.